Analisis Konsumsi Energi dan Emisi GRK terhadap Biaya Perusahaan Manufaktur di Indonesia - Sihombing, Septiana; Mahardi Lestari, Dian; Fitriani Nasution, Mutiah; Eva Rini, Lamia (Journal of Community Development and Disaster Management, 2025)
This study aims to analyze the impact of fossil fuel and electricity consumption on total costs, with greenhouse gas (GHG) emissions as an intervening variable in manufacturing firms in Indonesia. The manufacturing industry is one of the largest energy consumers, significantly contributing to GHG emissions and increasing environmental concerns. This study uses secondary data from the Central Bureau of Statistics (BPS) from 2020 to 2023, covering 96 manufacturing firms selected through purposive sampling. Data analysis was conducted using regression with path analysis through WarpPLS 7.0 software. The results show that: (1) GHG emissions have a positive and significant effect on coal, diesel, and other fuels (gasoline, kerosene, lubricants), a negative and significant effect on electricity, and a positive and significant effect on gas. (2) Total costs have a positive but insignificant effect on coal and diesel, a negative but insignificant effect on gas and other fuels (gasoline, kerosene, lubricants), and a negative and significant effect on GHG emissions. (3) Total costs through GHG emissions have a positive and significant influence on coal and diesel, a negative and insignificant effect on gas and other fuels, and a negative and significant effect on electricity. This study contributes to understanding how energy consumption affects corporate expenses and environmental impact. The findings suggest that increasing electricity use and reducing fossil fuel consumption can help lower emissions and optimize costs. Future research should explore the impact of government incentives on corporate energy efficiency strategies.